2023
DOI: 10.1186/s12905-023-02497-8
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of term premature rupture of membrane: case-control study in Saint Paul’s Millennium Medical College Hospital, Addis Ababa, Ethiopia

Abstract: Background The term premature rupture of the membranes is the rupture of the membranes before the onset of labor beyond 37 weeks of gestation. Several factors, including obstetric, gynecologic, socioeconomic, and medical, are identified as potential risk factors. This clinical event has detrimental maternal and neonatal complications. Objectives This study aimed to investigate the determinants of the term premature rupture of the membranes in Ethio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Previois data showed that 4.91% of pregnancies had amniotic fluid discharge issues [2]. Many measures have been taken to address it, but it remains unresolved [3], [4]. According to the findings of the perinatal maternal audit, preeclampsia, infection, diabetes mellitus, heart disease, brain tumors, and hemorrhage were the most common diagnoses for reasons of maternal death in Sleman Regency [5].…”
Section: Introductionmentioning
confidence: 99%
“…Previois data showed that 4.91% of pregnancies had amniotic fluid discharge issues [2]. Many measures have been taken to address it, but it remains unresolved [3], [4]. According to the findings of the perinatal maternal audit, preeclampsia, infection, diabetes mellitus, heart disease, brain tumors, and hemorrhage were the most common diagnoses for reasons of maternal death in Sleman Regency [5].…”
Section: Introductionmentioning
confidence: 99%